Association of genetic variability in CD209 gene with bovine paratuberculosis disease: a case–control study in the Indian cattle population. Issue 4 (1st August 2022) - Kumar, Satish; Kumar, Subodh; Singh, Ran Vir; Chauhan, Anuj; Kumar, Amit; Bharati, Jaya; Singh, Shoor Vir
Abstract: This study aimed to explore the association of single nucleotide polymorphisms (SNPs) in CD209 gene with the occurrence of bovine paratuberculosis (PTB) disease caused by Mycobacterium avium subspecies paratuberculosis ( MAP ) in Indian cattle. A total of 213 animals were preliminarily selected on the basis of physical body condition score, which was then screened by a panel of diagnostic tests viz. Johnin, ELISA, fecal microscopy, and fecal culture, for the establishment of a case–control resource population. A total of four SNPs viz. rs208222804, rs211654540, rs208814257, and rs210748127 in CD209 gene were genotyped by PCR-RFLP. All SNPs, except rs210748127, were polymorphic in our population. Genotypic–phenotypic associations were assessed by the PROCLOGISTIC procedure of SAS 9.3. The SNP rs208814257 yielded three genotypes viz. CC, CG, and GG, which were significantly ( p  < 0.05) different in case as compared to the control population. The odds of CC and CG in comparison to GG genotype were 1.21 and 0.40, respectively. The CG genotype was significantly higher in control population, indicating that this genotype may provide resistance against PTB in our resource population. Upon validation in an independent, larger test population and following biological characterization, SNP rs208814257 can be incorporated in marker panel for selection of animals with greater resistance to MAP infection.